Injuri profile in children and adolescents (10 to 18 years) according to their biological age and level of sports participation - Silva, Lara Raquel Pimentel Costa e (2019)
Physical activity (PA) is beneficial, enhancing healthy development. However, participation in PA involves a risk of injury that has a considerable public health impact. There are physical and physiological differences between children and adults related to growth and development that may cause children to be more vulnerable to injury. This means that the demands of sports practice can overlap with growth and maturation, creating a favorable environment for injury occurrence. The present dissertation presents five articles that study sports injuries in Portuguese children and adolescents and its association with predictors such as maturation, decimal age, PA level (defined by type and volume of PA), intensity of PA, health related quality of life (HRQoL) and parental instruction, variables poorly studied in this context. In the first study, the extent of the problem was determined. Injury prevalence of and its profile was set, and the first approach to risk factors was done. The results were expressive and comparable to those recorded in European countries and in the United States of America. They were mostly benign conditions but the severity and residual effects were already significant. The injury occurrence increased with age and was higher in federated athletes and school sports. The second and third studies determined the influence of decimal age, maturation and PA level on injury occurrence, injury rate, injury type and body area injury location in both sexes. The results showed that all PA levels influence injury occurence and its profile. Maturation was a strong injury predictor, especially in girls. We also concluded that chronological age may not be an absolute indicator for injury risk at this specific stage. Maturation assessment appears to be a more accurate indicator. Study four replicated the model presented in study two and three, but instead of considering PA level, considered PA intensity. The results showed that PA intensity is also an injury predictor, with expression over injury profile. Study five explored the effects of biossocial variables – HRQoL and parental instruction. Results showed that three dimensions of KIDSCREEEN-52 and the level of parental instruction are associated with injury and its profile. The present work provided evidence that injury etiology in Portuguese children and adolescents is multifactorial, being associated with maturational, biosocial and load variables (type, volume and intensity of PA). These data may be relevant for injury risk stratification at this specific stage of growth. It may also provide indicators to consider the different levels and intensities of PA, thus contributing to the prevention of injuries.